2003
DOI: 10.1002/eji.200323682
|View full text |Cite
|
Sign up to set email alerts
|

Vav exchange factor counteracts the HIV‐1 Nef‐mediated decrease of plasma membrane GM1 and NF‐AT activity in T cells

Abstract: Several findings support the importance of GM1-enriched lipid microdomains of plasma membrane and of Vav, an essential regulator of actin cytoskeletal rearrangement, in the regulation of T cell activation. Moreover, a functional link among lipid microdomains, Vav and the HIV product Nef has been described. These observations suggest that Nef can modify plasma membrane GM1, affecting the behavior of HIV-infected cells towards antigen recognition and Vav towards counteracting such an effect. We observed that Nef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Some studies suggest involvement of Nef in HIV-mediated enhancement of NF-κB induction [60], while others did not observe NF-κB activation when Nef was expressed in the absence of other HIV proteins [61,62]. Therefore, detection of NF-κB in 5C Nef immunocomplexes from sorted cells may reflect cytoplasmic retention of NF-κB [13], rather than specific association of NF-κB with Nef.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggest involvement of Nef in HIV-mediated enhancement of NF-κB induction [60], while others did not observe NF-κB activation when Nef was expressed in the absence of other HIV proteins [61,62]. Therefore, detection of NF-κB in 5C Nef immunocomplexes from sorted cells may reflect cytoplasmic retention of NF-κB [13], rather than specific association of NF-κB with Nef.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with these results, inhibition of NFAT-driven luciferase was observed when Jurkat T cells were transfected with a Nef-CD8 fusion protein and stimulated with peptide-pulsed APC [56]. Of interest, this function was associated with Nef-mediated modulation of Vav, possibly using PAK2 as an intermediary.…”
Section: Regulation Of Key Transcription Factors and Signaling Moleculementioning
confidence: 99%
“…By contrast, later studies have employed anti-CD3 and anti-CD28 that are either cross-linked [39,40,42,44,53], presented on beads [45,66,159] or bound to coverglass to mimic the immune synapse [86]; however, the stimulation dose in these assays may not reflect biological interactions with APC. This limitation may be overcome by activating T cells with peptide-pulsed APCs [45,46,56]. It would be of interest to systematically investigate whether reagents or dose can contribute to divergent findings.…”
Section: Making Sense Of Discrepancies In the Literaturementioning
confidence: 99%
“…These initial observation initiated numerous studies to address extend, mechanism and functional consequence of alterations of TCR signaling by HIV-1 Nef. Presumably due to the use of varying experimental strategies that often involved the use of immortalized cell lines rather than primary cells and marked overexpression of individual proteins, these efforts yielded sometimes contradicting results but generally concluded that HIV-1 Nef inhibits T-cell activation [72-75]. More recent work, including studies based on viral infection of primary target T-cells, revealed that HIV-1 Nef moderately enhances distal responses to exogenous TCR stimulation by mitogens or anti-TCR Abs including enhanced induction of NFAT, NFκB, AP-1 transcriptional activity, the release of calcium, and IL-2 production [50,76-88].…”
Section: Introductionmentioning
confidence: 99%